2017
DOI: 10.1515/revneuro-2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

How neuroscience can inform the study of individual differences in cognitive abilities

Abstract: AbstractTheories of human mental abilities should be consistent with what is known in neuroscience. Currently, tests of human mental abilities are modeled by cognitive constructs such as attention, working memory, and speed of information processing. These constructs are in turn related to a single general ability. However, brains are very complex systems and whether most of the variability between the operations of different brains can be ascribed to a single factor is questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 236 publications
0
16
0
Order By: Relevance
“…Neuropsychological tests have traditionally been evaluated by methods related to brain function (e.g., Delis et al, 2004). Studies employing methodology that relates to brain function have shown that CHC constructs can be dissociated on the basis of test content (McFarland, 2017b). For example, Volle et al (2008) used both fMRI and lesion mapping to dissociate frontal regions associated with verbal and spatial working memory.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropsychological tests have traditionally been evaluated by methods related to brain function (e.g., Delis et al, 2004). Studies employing methodology that relates to brain function have shown that CHC constructs can be dissociated on the basis of test content (McFarland, 2017b). For example, Volle et al (2008) used both fMRI and lesion mapping to dissociate frontal regions associated with verbal and spatial working memory.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of factor analysis and structural modeling have been used to argue for test validity (Thompson & Daniel, 1996), selection of useful models require constraints by information external to the test batteries being evaluated. These external constraints include the extent to which models allow for accurate prediction of alternative indices of the construct that they are intended to represent (i.e., convergent and discriminant validity, (Campbell and Fisk, 1959)) and the extent to which they are consistent with what is known of brain functioning (McFarland, in press). …”
Section: Discussionmentioning
confidence: 99%
“…In this latter regard, McFarland [55] published a review article answering the next question: how can neuroscience inform the study of individual differences in cognitive abilities? After discussing several lines of evidence, he arrived at the conclusion that: “ brain networks might best be characterized in terms of the information they process rather than in terms of abstract psychological processes such as working memory and executive control ”.…”
Section: Cognition and Brain Network: Summary Discussion And Inmentioning
confidence: 99%